2010
DOI: 10.1108/14777831011049106
|View full text |Cite
|
Sign up to set email alerts
|

Good environmental practices for hospitality and tourism

Abstract: PurposeThere is a consensus about the negative effects of transportation and some activities related to hospitality on the environment. In this sense, several proposals have been pointed out to pursue environmental sustainability of tourism activities and minimize their impact on climate change. In particular, some applications of information and communication technologies (ICT) have a direct contribution to the reduction of the demand of supplies and energy by the hospitality industry. The present paper has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…In line with our first hypothesis, the five-star hotels exhibited a degree of implementation 96 points higher than both three- and four-star establishments[7]. Ruiz‐Molina et al (2010) reported a similar divide between five- and three-/four-star hotels attributed to the greater availability of resources in higher-category hotels and to three-star hotels’ strong bid in trying to equal four-star establishments in terms of implementation of new technologies. Other studies have also reported on the importance of category (number of stars) in regards to hotel pricing and competitiveness (Becerra et al , 2013) as well as its specific impact on RM penetration (Abrate et al , 2012; Oliveira et al , 2013; Xiaowen et al , 2013; Talón-Ballestero and González-Serrano, 2013).…”
Section: Determinants Of the Degree Of Rm Implementation: Results And Discussionsupporting
confidence: 75%
“…In line with our first hypothesis, the five-star hotels exhibited a degree of implementation 96 points higher than both three- and four-star establishments[7]. Ruiz‐Molina et al (2010) reported a similar divide between five- and three-/four-star hotels attributed to the greater availability of resources in higher-category hotels and to three-star hotels’ strong bid in trying to equal four-star establishments in terms of implementation of new technologies. Other studies have also reported on the importance of category (number of stars) in regards to hotel pricing and competitiveness (Becerra et al , 2013) as well as its specific impact on RM penetration (Abrate et al , 2012; Oliveira et al , 2013; Xiaowen et al , 2013; Talón-Ballestero and González-Serrano, 2013).…”
Section: Determinants Of the Degree Of Rm Implementation: Results And Discussionsupporting
confidence: 75%
“…The connection between technology and sustainability in (sports) tourism can be closely linked to the use of renewable energies. In this area, reference is made to the work of Yaw [40] and Ruiz-Molina, Gil-Saura, and Moliner-Velázquez [41] as examples. Regarding the dimension of policy, reference is made to the importance of internationally recognized rules for tourism [42], especially the interaction of different stakeholders in destinations as a network [43][44][45].…”
Section: Sustainability In Sports Tourismmentioning
confidence: 99%
“…Anyway, all tourism transaction as transportation and activities related to hospitality may be hindrances in undertaking the environmental sustainability of tourism systems. The application of online booking and promotion, information and management systems transmission, other mode of internet-based tourism activities as ICT systems, AI and GPS that are connected to hospitality and tourism providers may help these companies decrease their environmental and cultural impact [27]. Interpretation plays an important role in the tourism industry.…”
Section: Selective Literature Review and The Choice Of Variables For The Model 21 Interpretationmentioning
confidence: 99%